Globalization and environment: discourse, policies and practice - Manish K Verma, Ed (Rawat, 2015)
The inordinate process of globalization has seen an intense movement of the world on social, cultural, economic, political and ecological fronts leading to integration, unification, homogenization and transformation of society and environment at the global level. Due to its enduring and manifold impacts, scholars are having varied perceptions about the nature, magnitude, discourse, policies and practices associated with globalization. It is an important issue of concern whether to consider it benign and a blessing or a curse for mankind. Nevertheless, the way globalization process has operated during the last couple of decades, it has become clear that it is an evolving reality. Its contours have changed significantly in due course of its evolution and diffusion at global level. Keeping above perspectives as the backdrop, through the edited volume, the effort is to debunk the enigma associated with the process of globalization, and to understand comprehensively the inter-linkages between globalization, environment and society by taking into consideration, the strands of ‘emerging discourse’, ‘ecological dimension’, ‘social dimension’ and ‘economic dimension’. Each strand of thought, mentioned above, is an attempt to shed light on one major area of debate evolved at the global level due to advent of globalization, taking into account the viewpoints of the eminent scholars.